2022
DOI: 10.1002/acm2.13840
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of preplan‐based three‐dimensional individual template‐guided brachytherapy compared to freehand implantation

Abstract: Image‐guided adaptive intracavitary/interstitial brachytherapy (IC/IS IGABT) has exhibited superior dosimetry advantage and local control for locally advanced cervical cancer (LACC). Our group designed a type of cylindrical three‐dimensional (3D) printed vaginal template combining an intracavitary applicator with straight and oblique interstitial needles according to the preplan on computed tomography images. This work aimed to research the consistency of the preplan with the treatment plan at every fraction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…The D 90 of HR-CTV and IR-CTV in the ST group were increased to 3.58% (p = 0.031) and 10.22% (p = 0.002) compared with the FH group, while D 2cc of the bladder and sigmoid were lower than those in the FH group (p < 0.05). These dosimetric results of 3D standardized template were similar to previous reports, in which individualized templates were mainly used [6][7][8][16][17][18][19][20]. Furthermore, the mean value of CI in this study was significantly improved by 23.21% in the ST group compared with the FH group (p < 0.001).…”
Section: Table 3 Spearman's Correlation Analysis Between Geometric Pa...supporting
confidence: 90%
See 1 more Smart Citation
“…The D 90 of HR-CTV and IR-CTV in the ST group were increased to 3.58% (p = 0.031) and 10.22% (p = 0.002) compared with the FH group, while D 2cc of the bladder and sigmoid were lower than those in the FH group (p < 0.05). These dosimetric results of 3D standardized template were similar to previous reports, in which individualized templates were mainly used [6][7][8][16][17][18][19][20]. Furthermore, the mean value of CI in this study was significantly improved by 23.21% in the ST group compared with the FH group (p < 0.001).…”
Section: Table 3 Spearman's Correlation Analysis Between Geometric Pa...supporting
confidence: 90%
“…Recently, several studies [ 7 , 16 , 17 ] have reported the use of 3D-printed templates for IC/ISBT, proposing patient-specific applicators, novel applicator designs, and optimized source trajectories. These prior published experiences tend to focus on using an individualized template for each patient with the lack of widespread clinical use of IC/ISBT technology.…”
Section: Discussionmentioning
confidence: 99%
“…Lindegaard et al used a Vienna-style 3D-printed intra-vaginal template (without a ring channel) to combine a tandem with both straight and oblique needles [30]. Several authors reported using 3D-printing to produce intra-vaginal cylindrical templates for curved IS needles with or without the use of a central channel to accommodate a metallic fixation rod or an intra-uterine tandem [31][32][33][34][35][36]. Logar et al modified a T&R IC applicator with a 3D-printed add-on, resulting in a Vienna-style IC/IS applicator with straight and oblique IS needles [37].…”
Section: Purposementioning
confidence: 99%